2022
DOI: 10.23917/jisel.v5i1.16764
|View full text |Cite
|
Sign up to set email alerts
|

Islamic Insurance in Indonesia: Opportunities and Challenges on Developing the Industry

Abstract: Islamic insurance is a minor industry compared with other Islamic financial institutions in Indonesia. However, it has enormous potential to grow together with its challenges. This study aims to analyze the opportunities and challenges of the Islamic insurance industry in Indonesia. This research uses a qualitative methodology and descriptive analysis. The result summarizes that the possibilities are:  domino effect from Halal Value Chain and other development of government-owned enterprises; digitalization in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 15 publications
0
0
0
Order By: Relevance
“…Taraflar arasında risklerin paylaşılmasını esas alan Tekâful sigortacılık modelini dijital teknolojilerle çiftçilere sunmaktadır. Dijital teknolojilerle, Tekâful operasyonlarını otomatikleşebilir, Tekâful sigorta modelini talep eden tarım işletmecileri için, tarım sektöründeki risklerin daha etkin bir şekilde yönetilmesini sağlanabilir (Maf 'ula ve Mi'raj, 2022).…”
Section: Tarimda Fi̇nansal Teknoloji̇ler (Agri-fintech)unclassified
“…Taraflar arasında risklerin paylaşılmasını esas alan Tekâful sigortacılık modelini dijital teknolojilerle çiftçilere sunmaktadır. Dijital teknolojilerle, Tekâful operasyonlarını otomatikleşebilir, Tekâful sigorta modelini talep eden tarım işletmecileri için, tarım sektöründeki risklerin daha etkin bir şekilde yönetilmesini sağlanabilir (Maf 'ula ve Mi'raj, 2022).…”
Section: Tarimda Fi̇nansal Teknoloji̇ler (Agri-fintech)unclassified
“…This study recommends strengthening the implementation of corporate governance to increase the attractiveness of Islamic insurance companies and have an impact on customer satisfaction and customer loyalty. Maf'ula & Mi'raj (2022) analyzed the opportunities and challenges of the Islamic insurance industry in Indonesia. The results of the study concluded that the possibilities that might occur are: the domino effect of the Halal Value Chain and the development of other state-owned enterprises; digitalization in the field of Islamic Finance; and the potential market for micro Islamic insurance.…”
Section: Hierarchy Chartmentioning
confidence: 99%
“…Asuransi syariah di Indonesia dinilai memiliki pangsa pasar yang kecil dibandingkan lembaga keuangan syariah lainnya (Maf'ula & Mi'raj, 2022). Meskipun terus mengalami perkembangan, pada kenyataannya hal ini tidak di iringi dengan pemahaman kesadaran untuk melakukan proteksi diri dari risiko.…”
unclassified